Service utilization and osts associated with switching to risperidone from previous treatment with typical antipsychotic agents - Sulaiman, Ahmad Hatim; Tan, J.; Ayu, M.A.S.; Habil, Mohd Hussain (Malaysian Psychiatric Association, 2010)
This study determined medical service utilization and costs associated with switching to risperidone from previous treatment with typical antipsychotic agents. 62 adult outpatients diagnosed with schizophrenia were identified from pharmacy records, with complete information regarding medical service utilization for one year before and after treatment with risperidone. Information on hospitalization, use of day care hospital, electroconvulsive therapy, emergency department, outpatient clinic services and functional parameters were collected. Cost of treatment, cost of unemployment and cost of lost productivity due to suicide were calculated. The results showed significant fewer hospitalization days, ECT sessions and emergency department visits were observed one year after switching to risperidone